Prediction of mortality in NICU of tertiary care rural hospital by using Snappe- II - Chaudhary , Shruti; Varma, Ashish (International Journal of Psychosocial Rehabilitation, 2020)
Neonatal mortality is very high in India. The complains of neonatal illnesses are not that obvious, so by the time an illness is diagnosed, the neonates become critically ill. Hence, an objective scale is required. To predict mortality of neonates in NICU by using SNAPPE II. To study correlation of snappe II score and mortality of neonates. The study was conducted in Neonatal ICU of Jawaharlal Neharu Medical College and AVBRH ,Sawangi (M) , WardhaDuration of study: 2 years .From August 2018 to June 2020Sample size : 50Type of study : Prospective observational studyEthical Committee approval : The Institutional Ethical Committee permission was sought to conduct this study before data collection.Inclusion criteria : All newborns coming to NICU with birth weight < 1500 gm Exclusion criteria :Neonates going discharged against medical advice and referred patients.Congenital malformationsProcedure of study : All patients getting admitted to NICU with <1500 gms were examined for following 9 parameters to award specific points depending on observations on neonatal reports within first 12 hours of NICU stay. Depending on those points we got cumulative score by summation of points of these 9 parameters. The neonates who had higher score was considered to be more prone for mortality. Our prediction and the actual outcome in the form of survival and non-survival was compared. Findings will be encouraging to use SNAPPE II Scores for assessments of neonates in NICU.